Improved retransplant outcomes: early evidence of the share35 impact. Issue 7 (July 2018) - Brooks, Joseph T.; Koizumi, Naoru; Neglia, Elizabeth; Gdoura, Bilel; Wong, Tina W.; Kwon, Chang; Smith, Tony E.; Ortiz, Jorge
Abstract: Background: Share 35 prioritizes offers of deceased donor livers to regional candidates with Model for End-Stage Liver Disease (MELD) ≥35 over local candidates with lower MELD scores. Analysis of Share35 has shown that overall 1- or 2-year post-transplant (LTx) outcomes have been unchanged while waitlist mortality has been reduced. However, these studies exclude retransplant (reLTx) recipients. This study aims to investigate the outcomes of liver retransplants in evaluating the impact of the Share35 policy. Methods: A retrospective analysis of data from the United Network for Organ Sharing database over the period June 2011–June 2015 was performed. Results: A total of 19, 748 LTx and 312 reLTx recipients were identified. Of the LTx recipients, 9626 (48.7%) underwent transplant pre-Share 35 and 10, 122 (51.3%) post-Share 35. 123 (39.4%) reLTx recipients underwent retransplantation pre-Share 35 and 189 (60.6%) post-Share 35. ReLTx recipients experienced improved 2-year graft survival post-Share 35 compared to pre-Share 35 (67% vs. 21.1%). Patient survival also improved at 2-years for reLTx recipients post-Share 35 compared to pre-Share 35 (69.2% vs. 33.1%). Transplant post-Share 35 was protective for both 2-year graft (HR = 0.669, CI = 0.454–0.985, p = 0.04) and patient (HR = 0.659, CI = 0.44–0.987, p = 0.003) survival. Conclusion: Share35 is associated with improved outcomes after retransplantation.